1993
DOI: 10.1016/0140-6736(93)90636-u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human growth hormone therapy on melanocytic naevi

Abstract: Melanocytic naevi may grow more rapidly during human growth hormone (hGH) therapy. With standardised skin photographs, the growth rate of the naevi was two-fold greater in 14 hypopituitary and 5 Turner's syndrome girls treated with hGH than in untreated patients or controls. HMB-45 immunoreactivity, a marker of stimulated melanocytes, was absent in naevi from 18 of 19 individuals not treated with hGH, including 5 Turner's syndrome patients studied 2-43 months after stopping hGH. In naevi from 39 hGH-treated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 6 publications
1
47
0
1
Order By: Relevance
“…In another series no increase was found in the number of large nevi [4]and, as observed in the general population, the number of nevi increased with age and was increased in individuals with fair skin. Histologic studies have reported no increase in dysplastic features [10, 11]. The presumption therefore would be that whatever genetic factor(s) are operative they simply cause an increase in the number of typical nevi.…”
Section: Discussionmentioning
confidence: 99%
“…In another series no increase was found in the number of large nevi [4]and, as observed in the general population, the number of nevi increased with age and was increased in individuals with fair skin. Histologic studies have reported no increase in dysplastic features [10, 11]. The presumption therefore would be that whatever genetic factor(s) are operative they simply cause an increase in the number of typical nevi.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with GH may trigger melanocyte growth, but it has been shown neither to increase the number of nevi nor to trigger malignant transformation (393, 408,409). No clear relationship has been found between GH therapy and other skin lesions (399).…”
Section: Dermatologymentioning
confidence: 99%
“…Thus, not only systemic but also paracrine and/or autocrine cutaneous activity of the GH-IGF system contributes to skin homeostasis [11][12][13][14][15]. GH supplementation induces skin changes [16][17][18][19][20][21], a part of which may correspond to some corrective effects on ageing skin [22].…”
Section: Ageing Of the Endocrine Systemmentioning
confidence: 99%